Are People Inequality Averse, and Do They Prefer Redistribution by the State? Evidence From German Longitudinal Data on Life Satisfaction - Johannes Schwarze; Marco Härpfer (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
We link life-satisfaction data to inequality of the pre-government income distribution at the regional level, to estimate the degree of inequality aversion. In addition, we investigate whether a reduction in inequality by the state increases individual well-being. We find that Germans are inequality averse over the entire income distribution. However, inequality reduction by the state does not increase well-being. On the contrary, inequality reduction places something of an excess burden on middle-income earners. The paper uses data from the German Socio-economic Panel Study (GSOEP) from 1985 to 1998.
Keywords: D31; D63; I31; C23; 330; Inequality aversion; redistribution; life satisfaction; panel data; Einkommensverteilung; Soziale Werte; Einkommensumverteilung; Lebensqualität; Schätzung; Deutschland; Lebenszufriedenheit